Lecciones del mundial Brasil 2014: Goles y autogoles de las organizaciones desde las teorías de liderazgo y de los recursos y capacidades. (2014)
This paper analyses elements of organizational theory related to World Cup Brazil 2014 results. Participants’ performance is used to explain several theories that might explain successes and failures of each country. The main issues of the theory of resources and capabilities and leadership theories are applied. It is remarkable that there are multiple possibilities to understand the final rankings of the event from the bases of theory of resources, by extending the analysis to the perspective of competitive advantage. Finally, conclusions on the champion team and relationships between theories and results are summarized.